ROLE PLAYING ACTIVITY FOR STUDENTS IN NON-ENGLISH STUDY PROGRAM - Irene Brainnita Oktarin (IKIP PGRI Bojonegoro, 2019)
Abstract: The researcher conducted research about role playing activity in English for business at Gentiaras College. English for business is a compulsory subject for non-English study program. The purposes of this research were to identify the students’ attitude toward role palying activity in the class and the implementation of role play in the class. The participants of this research were 25 students from management study program who took English for business subject. Questionnaire and interview were used for collecting the data. Those data were then analyzed and tabulated. The result of this study is most students have positive attitudes to role playing activity during studying English for business. Given situation based on the topics and playing the role in the class makes the students more motivated to speak English. This activity facilitates them to improve and practice their English speaking ability. Keywords: Role playing, English for business, students’ attitude Abstrak: Peneliti melakukan penelitian tentang aktivitas bermain peran dalam Bahasa Inggris untuk bisnis di STIE Gentiaras. Bahasa Inggris untuk bisnis adalah mata pelajaran wajib untuk program studi non-Bahasa Inggris. Tujuan dari penelitian ini adalah untuk mengidentifikasi sikap mahasiswa terhadap aktivitas bermain peran di kelas dan pelaksanaan bermain peran di kelas. Partisipan dalam penelitian ini adalah 25 mahasiswa dari program studi manajemen yang mengambil mata kuliah Bahasa Inggris untuk bisnis. Kuesioner dan wawancara digunakan untuk mengumpulkan data. Data-data itu kemudian dianalisis dan ditabulasi. Hasil dari penelitian ini adalah sebagian besar mahasiswa memiliki sikap positif terhadap aktivitas bermain peran selama belajar Bahasa Inggris untuk bisnis. Situasi yang diberikan berdasarkan pada topik dan memainkan peran di kelas membuat mahasiswa lebih termotivasi untuk berbicara bahasa Inggris. Kegiatan ini memfasilitasi mereka untuk meningkatkan dan melatih kemampuan berbahasa Inggris mereka. Kata Kunci: Bermain peran, bahasa Inggris untuk bisnis, sikap mahasiswa